PENGARUH HEEL RAISE EXERCIE DAN KINESIOTAPING TERHADAP PENINGKATAN KEMAMPUAN FUNGSIONAL FACIITIS PLANTARIS AKIBAT PENGGUNAAN SEPATU DINAS DI BATALYON A JAKARTA - Pramesthi, Daffiela Sekar; Laksono, Abdurrahman Berbudi Bowo; Trioclarise, Rovika (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Background: Plantar fasciitis is a painful condition in the heel that occurs due to overuse or microtrauma to the plantar fascia. The incidence rate of planttaris fasciitis reaches 15% of the population of the Jakarta Battalion A Unit. One of the risk factors for Faciitis Plantaris is the regular use of shoes for field work resulting in a decrease in functional ability. This study aims to determine the effect of giving heel raise exercise and kinesiotaping on increasing functional abilities in service shoe users at the Mobile Brigade Unit Battalion A Jakarta. Methods: This study used a pre-experimental design with one group pretest and posttest design with 14 respondents. The training program is held 12 times in 4 weeks. Measurement of functional ability in runners was carried out by answering questions. Results: tained an average value of functional ability before the intervention was 49.66 and after the intervention was 60.72, and the hipotesis to obtain a p of 0.000. Conclusion: Heel raise exercise and kinesiotaping have an effect on increasing functional abilities in service shoe wearers in the Brimob Battalion A Unit with plantaris fasciitis.